Risk of hypersensitivity pneumonitis and interstitial lung diseases among pigeon breeders. Issue 3 (26th May 2016) - Cramer, Christine; Schlünssen, Vivi; Bendstrup, Elisabeth; Stokholm, Zara Ann; Vestergaard, Jesper Medom; Frydenberg, Morten; Kolstad, Henrik Albert
We studied the risk of hypersensitivity pneumonitis and other interstitial lung diseases (ILDs) among pigeon breeders. This is a retrospective follow-up study from 1980 to 2013 of 6920 pigeon breeders identified in the records of the Danish Racing Pigeon Association. They were compared with 276 800 individually matched referents randomly drawn from the Danish population. Hospital based diagnoses of hypersensitivity pneumonitis and other ILDs were identified in the National Patient Registry 1977–2013. Stratified Cox regression analyses estimated the hazard ratios (HR) of hypersensitivity pneumonitis and other ILDs adjusted for occupation, residence and redeemed prescription of medication with ILDs as a possible side-effect. Subjects were censored at death, emigration or a diagnosis of connective tissue disease. The overall incidence rate of ILD was 77.4 per 100 000 person-years among the pigeon breeders and 50.0 among the referents. This difference corresponded to an adjusted HR of 1.56 (95% CI 1.26–1.94). The adjusted HRs of hypersensitivity pneumonitis and other ILDs for pigeon breeders were 14.36 (95% CI 8.10–25.44) and 1.33 (95% CI 1.05–1.69), respectively. This study shows an increased risk of ILD among pigeon breeders compared with the referent population. Protective measures are recommended even though ILD leading to hospital contact remains rare among pigeon breeders. Pigeon breeders have an increased risk of interstitial lung diseases compared to the general population http://ow.ly/4neltu